BYSSINOSIS - Nakladalova, Marie (Biomedical papers, 2000)
Byssinosis as a nonspecific chronic respiratory disease in textile workers exposed to cotton, flax, jute, hemp andsisal is described. Opinions about aetiopathogenesis are presented. The following chapters are focused on clinicalsymptoms and functional lung changes. Classification of the disease is described afterwards. Finally, the necessityof medical and technical measures to prevent the development of this disease in textile workers is emphasised.
Keywords: Byssinosis / Textile industry